2016
DOI: 10.3892/or.2016.5279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the regulation of polysialyltransferase ST8SiaII on the invasiveness and metastasis of small cell lung cancer cells

Abstract: Invasiveness and metastasis may seriously affect the prognosis of small cell lung cancer (SCLC). In the present study, we analyzed the effects and inherent mechanisms of action of polysialic acid-modified neural cell adhesion molecule (NCAM) on the invasive and metastatic potential of SCLC. Gene transfection and short hairpin RNA (shRNA) interference were used to enhance or inhibit, respectively, the expression of polysialyltransferase ST8SiaII in the SCLC cell line H446. We studied in vitro positive or negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…It is interesting to note that PSA-NCAM can be shed and acts in its proximate environment [40]. It has also been reported that overexpression of ST8SIA2 can mediate tumor cell invasiveness of hepatocellular carcinoma and small cell lung cancer by regulating activity of the PI3K/Akt and FGFR pathways, respectively [41], [42]. In triple-negative breast cancer models, Hedgehog ligand secreted by tumor cells activates CAFs, leading to upregulation of ST8SIA2 expression [43].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that PSA-NCAM can be shed and acts in its proximate environment [40]. It has also been reported that overexpression of ST8SIA2 can mediate tumor cell invasiveness of hepatocellular carcinoma and small cell lung cancer by regulating activity of the PI3K/Akt and FGFR pathways, respectively [41], [42]. In triple-negative breast cancer models, Hedgehog ligand secreted by tumor cells activates CAFs, leading to upregulation of ST8SIA2 expression [43].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ST8Sia2 and ST8Sia4 has been shown to be elevated in the tumors of patients with astrocytoma, which correlates with an increase in polysialic acid that is linked to tumor invasiveness [ 54 ]. The increase in ST8Sia2 expression has also been correlated to increased phosphorylation levels of ERK1/2, MMP-9, and FGFR1, all leading to increased invasion and migration of cells in vitro [ 75 ]. On the other hand, the overexpression of ST8Sia4 has been shown to be positively correlated to multi-drug resistance in chronic myeloid leukemia by regulating the PI3K/Akt signaling pathway, leading to an increase in cell survival [ 55 ].…”
Section: Mechanisms Leading To Hypersialylationmentioning
confidence: 99%
“…This is closely correlated with poor prognosis in the clinic. [8][9][10][11][12][13][14] The polySTs, and ST8SiaII in particular (generally thought to be the dominant enzyme in tumours where polySia is expressed 8,15 ), have significant potential as drug targets in a number of difficult-to-treat cancers, notably neuroblastoma and small cell lung cancer. 8,16 A number of in vitro assays have been developed and reported for the evaluation of polyST enzyme activity, utilising the enzyme, the substrate CMP-sialic acid, and the acceptor NCAM.…”
Section: Introductionmentioning
confidence: 99%